SOCIALIZATION GOOD VIRTUAL COMMUNICATION IN USE OF DIGITAL MEDIA FOR PREVENT VIOLENCE AGAINST WOMEN AND CHILDREN - Safarwati, Meri; Supriadi, Supriadi; Haniza, Nurul (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2022)
Based on data released by KOMNAS HAM Perempuan, it is stated that : that during the violent covid-19 pandemic to woman show very sharp increase . Likewise with _ based violence _ cyber show significant increase . This show that mass violence good in realm public nor based on cyber is problem to be get attention from various party . Knowledge and understanding about shapes violence especially for women and children good in space public nor based on cyber is very necessary , for avoid happening violence good by direct nor virtually. Team of Lecturers and Students at Sahid University Jakarta in the SAPA forum ( Friends of Women and Children) carries out activity community service _ for Public around Sahid University Jakarta campus , in particular Public around RPTRA ( Public Space Integrated Child Friendly) which is located in Kelurahan Menteng In , District Tebet , South Jakarta. Activity held on January 17 , 2022. Because during the PPKM period, activities implemented online. Purpose activity devotion this is for give knowledge and understanding about shapes violence to women and children . With the knowledge he has expected could prevent happening violence . Activity devotion implemented in shape gift Theory online . who became partner is inhabitant around at a time RPTRA managers in general is people mother . In session first given Theory about shapes violence good by direct nor virtually , session second given given tips good virtual communication and avoid happening violence . Session third be delivered Theory about procedure reporting and complaints if acts of violence occur. After implementation measurement with done pretest and posttest show that activity devotion succeed add knowledge and understanding about shapes violence good in family , in public and violence cyber. This thing showed with there is difference Among score results posttest with results score pretest , score more posttest big compared with score results prestest .